Development of a 3D Printing Strategy to Improve the Level of Abstraction in the Generation of Orthogonal Projections - Alvarado-Silva, Carlos Alexis; Gastiaburú-Morales, Silvia Yvone; Gaytan-Reyna, Karina Liliana; Gaytan-Reyna, Sassy Emperatriz; de Azevedo Silva, Fernando [UNESP] (Richtmann Publishing, 2023)
Using the 3D printing method as an engineering teaching tool has been intensifying and implemented throughout all the courses of the engineering career and even in research departments, this means that it not only fulfills the functions for those that were originally designed (manufacturing of parts) but as a support for the acquisition of other important skills in future engineers. The research has a quantitative approach, experimental design with a control and experimental group of 35 and 37 students respectively. For its execution, a pre-test and post-test have been used as instruments, which were applied to students of a Technical Drawing subject of the career of Mechanical-Electrical Engineering. The findings reveal that the proposed teaching strategy using 3D printed elements significantly improves the level of abstraction for the generation of orthogonal projections. After the experiment, the control group showed an improvement in average grades of 20.3%, this indicates that the application of traditional teaching improves the level of abstraction. In the case of the experimental group, a higher average of the grades was obtained with a 30.8% improvement, which means that the students felt more comfortable with the proposed teaching strategy. On the other hand, the proposal was well received by the students who participated in the session, as they stated through the satisfaction survey that they were 90% between satisfied and very satisfied.
Keywords: 3D Print; Level of Abstraction; Orthogonal Projections; Technical Drawing